Beyond Milk and Nurture: Breastfeeding’s Powerful Impact on Breast Cancer - Mustafa, Muhammad; Sarfraz, Sadaf; Saleem, Gullelalah; Khan, Touqeer Ahmad; Shahid, Damiya; Taj, Saba; Amir, Noor (Geburtshilfe und Frauenheilkunde, 2024)
Breast cancer (BC) stands as a global concern, given its high incidence and impact on women’s mortality. This complex disease has roots in various risk factors, some modifiable and others not. Understanding and identifying these factors can be instrumental in both preventing BC and improving survival rates. Remarkably, women’s reproductive behaviors have emerged as critical determinants of BC susceptibility. Numerous studies have shed light on how aspects including age of menarche, first pregnancy and menopause along with number of pregnancies, hormone replacement therapies, can influence one’s risk of developing BC. Furthermore, the act of breastfeeding and its duration have shown an inverse relationship with BC risk. This review delves into the biological and molecular mechanisms associated with breastfeeding that contribute to BC protection. It highlights the role of endocrine processes triggered by suckling stimulation, the gradual onset of lactational amenorrhea, delayed weaning, reduced lifetime menstrual cycles, chromosomal repair mechanisms, and immunological events throughout the lactation cycle. These insights provide a potential explanation for the protective effects conferred by breastfeeding against breast carcinomas.
Keywords: breast cancer; breastfeeding; breast cancer risk; HAMLET